2021
DOI: 10.1155/2021/5579327
|View full text |Cite
|
Sign up to set email alerts
|

Renal-Protective Effects and Potential Mechanisms of Traditional Chinese Medicine after Ischemia-Reperfusion Injury

Abstract: Renal ischemia-reperfusion (I/R) injury mainly causes acute kidney injury (AKI) after renal transplantation, trauma, sepsis, and hypovolemic shock. Patients with renal I/R injury are frequently associated with a poor prognosis. Traditional Chinese medicine (TCM) has been used for the prevention and treatment of various diseases in China and other Asian countries for centuries. Many studies have shown the protective effect of TCM on renal I/R injury, due to its diverse bioactive components. The potential mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…With the progress of medical technology and the upgrading of management system, we can continuously obtain high health management quality. Foreign studies believe that [ 3 , 17 ] PDCA can greatly improve the standardization of hand hygiene and the qualified rate of disinfection and sterilization in the operating room, which is consistent with the conclusion of this study. Domestic research by Sun shujun [ 3 , 14 , 18 ] showed that the implementation of hand hygiene management based on PDCA can improve the awareness and compliance of hand hygiene knowledge of operating room nurses and is of great value in reducing operating room infection.…”
Section: Discussionsupporting
confidence: 91%
“…With the progress of medical technology and the upgrading of management system, we can continuously obtain high health management quality. Foreign studies believe that [ 3 , 17 ] PDCA can greatly improve the standardization of hand hygiene and the qualified rate of disinfection and sterilization in the operating room, which is consistent with the conclusion of this study. Domestic research by Sun shujun [ 3 , 14 , 18 ] showed that the implementation of hand hygiene management based on PDCA can improve the awareness and compliance of hand hygiene knowledge of operating room nurses and is of great value in reducing operating room infection.…”
Section: Discussionsupporting
confidence: 91%
“…Due to the ethical, legal, political, and administrative barriers associated with data sharing, it is difficult to merge data from multiple companies. Manuel proposed a distributed method of data extraction [8]. Distributed learning is defined as learning from data without leaving the hospital.…”
Section: 1mentioning
confidence: 99%
“…Research has revealed that traditional Chinese medicine monomers and gene knockout technology can improve LPS-induced multiple organ dysfunction, including heart, lung, brain, kidney, and other essential organs [ 11 ]. Both berberine and artesunate can protect against acute lung injury caused by LPS [ 12 , 13 ]. Concurrently, curcumin can effectively improve LPS-induced acute kidney injury [ 14 ].…”
Section: Introductionmentioning
confidence: 99%